2014
DOI: 10.7448/ias.17.1.18821
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic cryptococcal antigenemia is associated with mortality among HIV‐positive patients in Indonesia

Abstract: IntroductionPrevious studies, mostly from Africa, have shown that serum cryptococcal antigenemia may precede the development of cryptococcal meningitis and early death among patients with advanced HIV infection. We examined cryptococcal antigenemia as a risk factor for HIV-associated mortality in Indonesia, which is experiencing a rapidly growing HIV epidemic.MethodsWe included ART-naïve HIV patients with a CD4 cell count below 100 cells/μL and no signs of meningitis in an outpatient HIV clinic in Bandung, Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
42
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 20 publications
9
42
3
1
Order By: Relevance
“…The prevalence of cryptococcal antigenemia in this study (7.1%) is higher than rates reported from rural Uganda (5.8%) [12] and northeastern Tanzania (5%) [19] but similar to another study in South Africa (7%) [22] and also to a recently published study in Indonesia (7.1%) [14]. Other studies have shown that the diagnostic methods, host factors including prior receipt of ART, and seasonal changes may influence the prevalence in different settings [2, 12, 19, 2325].…”
Section: Discussionsupporting
confidence: 87%
“…The prevalence of cryptococcal antigenemia in this study (7.1%) is higher than rates reported from rural Uganda (5.8%) [12] and northeastern Tanzania (5%) [19] but similar to another study in South Africa (7%) [22] and also to a recently published study in Indonesia (7.1%) [14]. Other studies have shown that the diagnostic methods, host factors including prior receipt of ART, and seasonal changes may influence the prevalence in different settings [2, 12, 19, 2325].…”
Section: Discussionsupporting
confidence: 87%
“…More female patients 248 (57.4%) than males 184 (42.6%) were enrolled for our study and all the CrAg positive subjects were female 7 (100%). This is contrary to previous reports from studies where more males were enrolled and also found CrAg positive [15] [23]. Most of the patients in our study were in age group 29 -39 years and this observation is similar to findings in a previous research with 24 -40 years [27].…”
contrasting
confidence: 83%
“…Our observed overall low cryptococcal antigenaemia of 1.6% among treatment naïve HIV positive patients is comparable with previous reports from Shika in Nigeria 2.2 % [17], Tanzania 3% [18] and USA 2.9% [19]. However our overall prevalence value in this study is lower than some reports from Nnewi 13.1% [20] South east, and Benin12.7% [12] South south part of Nigeria as well as Kenya 11% [21], Uganda 5.7% [22], Indonesia 7.1% [23] and Thailand 9.2% [24]. The observed differences in prevalence rates of cryptoccocal antigen positivity among HIV infected persons in the various studies cited may be explained by differences in sample sizes as well as varying sensitivities and specificities with differing methodologies of used kits.…”
supporting
confidence: 82%
“…18 A study from Indonesia documented a weak correlation between CD4 cell counts and the titre of cryptococcal antigen. 19 Whereas in the present study there was no correlation; however, the titre of cryptococcal antigen could not be estimated due to limited resources.…”
Section: Discussioncontrasting
confidence: 50%